Altitude-induced changes in muscle contractile properties - Perrey, S.; Rupp, T. (High Altitude Medicine & Biology, 2008)
Because of its high energetic demand, skeletal muscle is sensitive to changes in the partial pressure of oxygen. Most human studies on in vivo skeletal muscle function during hypoxia were performed with voluntary contractions. However, skeletal muscle function is not only characterized by voluntary maximal or repeated force- generating capacity, but also by force generated by evoked muscle contractions (i.e., force-frequency properties). This mini-review reports on the effects of acute or prolonged exposure to hypoxia on human skeletal muscle performance and contractile properties. The latter depend on both the amount and type of contractile proteins and the efficiency of the cellular mechanism of excitation-contraction coupling. Observations on humans indicate that hypoxia (during simulated ascent or brief exposure) exerts modest influences on the membrane propagation of the muscle action potentials during voluntary contractions. Overall in humans, in physiological conditions, including that of climbing Mt. Everest, there is extraordinarily little that changes with regard to maximal force-generating capacity. Interestingly, it appears that the adaptations to chronic hypoxia minimize the effects on skeletal muscle dysfunction (i.e., impairment during fatigue resistance exercise and in muscle contractile properties) that may occur during acute hypoxia for some isolated muscle exercises. Only sustained isometric exercise exceeding a certain intensity (30% MVC) and causing substantial and sustained ischemia is not affected by acute hypoxia.